Diversity, Abundance, and Distribution of Ectomycorrhizal Fungi in Rajo Lelo Forest Park (Tahura), Central Bengkulu Regency - Anwar, Guswarni; Izzatul Jannah; Risky Hadi Wibowo; Parwito, Parwito (Asosiasi Mikoriza Indonesia, 2024)
Rajo Lelo Forest Park (TAHURA) is located in Tanjung Terdana Village, Pondok Kelapa District, Central Bengkulu Regency. This forest area is overgrown with various trees, including ectomycorrhizal host trees. A purposive sampling plot method was used on each found fungus to determine ectomycorrhizal species' diversity, abundance, and distribution. Five plots were used, each measuring 20 cm by 20 cm. The data collected from these plots revealed important information about the forest's ecological dynamics. We examined the samples to determine the types of ectomycorrhizal species and how they aided tree health and forest biodiversity. Fungi found in the plot were identified morphologically by comparing morphological characters to references. According to the results of the analysis, there are 118 individual fungi from nine species and seven families. The species diversity index is classified as moderate, at 1.61. Clitopilus sp. is 33.05% more abundant than any other ectomycorrhizal fungus. However, there are 0.85% fewer species of Scleroderma sp., Lactarius sp., and Macrolepiota sp. than any other species. The distribution index of ectomycorrhizal fungi in Rajo Lelo Forest Park is 1.34, placing them in the clustering category.